ST elevated myocardial infarction: clinical manifestation and outcomes of thrombolysis in a tertiary care hospital - M. S., Ravishankar; S., Harish Kumar (International Journal of Advances in Medicine, 2018)
Background: Acute myocardial infarction has reached enormous proportion in the developing countries and it is speculated that atherosclerotic heart disease will replace infectious disease as the leading cause of death in India. It has been shown that the thrombolytic therapy is underutilized. So, the study was taken to study the clinical manifestations and outcome of thrombolytic therapy in STEMI. Methods: The study was conducted for a period of 18 months in a tertiary care centre during which 100 cases of STEMI admitted to ICCU were included in the study, after fulfilling the inclusion criteria for thrombolysis, data related to clinical profile and outcome of thrombolysis was collected. SPSS 16 was used to analyse the data. Descriptive statistics like proportions mean and SD were computed. Results: Incidence of STEMI was high among subjects in the age group 51-60 years. Males were more affected (72%). Smoking, hypertension, hyperlipidemia and diabetes mellitus were the most common risk factors. Chest pain (92%) was the most common symptom. Majority (56%) were admitted within 6 hours of onset of symptoms. Anterior wall infarction was most common type of myocardial infarction. Majority (82%) were admitted in either Killips I/II class. Left Ventricular failure and Arrhythmias were most common complication. 64% patients had objective evidence in a form of ECG with ST-T resolution (>50%) between 1-6 hours, 18% between 6-24 hours and 18% patients had no significant resolution even after 24 hours. Echocardiography showed good left ventricle function (LVEF >45%) in 70% and 30% of the patients showed reduced ejection fraction (LVEF<45%). Mortality was seen in 8% of cases. Conclusions: Smoking, hyperlipidemia, diabetes mellitus and hypertension were most important risk factors for MI in the study. Coronary pain relief was most frequent and early marker of reperfusion. The ST segment elevation resolution has been widely accepted as most reliable objective criteria of coronary reperfusion. Hence ST segment resolution is regarded as a marker of salvaged myocardium by post-thrombolytic reperfusion. Early reperfusion of the ischaemic myocardial tissue with thrombolytic therapy decreases the morbidity and mortality.